Religious Moderation of Millennial Generation at Islamic Higher Education in Eastern Indonesia - Zuhri, Barsihannor; Tahir, Gustia; Arbianingsih, Arbianingsih; Aksa, Aksa (IAIN Ponorogo, 2023)
This research examines the religious moderation of the millennial generation in Islamic Higher Education in Eastern Indonesia and identifies the most dominant factors contributing to religious moderation. Cross-Sectional Study (CSS) method measures religious moderation through four pillars at the same time: national commitment, religious tolerance, conflict avoidance (non-violence) and accommodation of local culture. The respondents of this research are millennial generations studying at the Islamic Higher Education in Eastern Indonesia. This research used the Consecutive Sampling with a total sample of 592 people. The research results show that religious moderation among millennial students in Eastern Indonesia is categorized as low concerning national commitment, religious tolerance, avoiding conflict (non-violence), and accommodation of local culture. The most dominant factors influencing the religious moderation of the millennial generation are social media and religious extra-campus curriculum.